(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
In this article, the famous work "Rawzat al-Safa" created by the historian Mirkhand, who created in the 15th century, describes the socio-economic, political and cultural history of Movarounnahr and Khurasan from the creation of mankind to the Timurid period, in which the geographical place names of Movarounnahr and Khurasan, information about rivers, mountains and deserts is given.